Activist scholar selected works of Marilyn Gittell - Gittell, Marilyn (Sage, 2012)
"Activist Scholar highlights Professor Gittell's writings on community organizations, citizen participation, urban politics, the politics of education, and gender. She specialized in applied and comparative research on local, regional, national, and international policies and politics, and placed a high priority on training researchers and scholars. Marilyn Gittell was a mentor to hundreds of students in the City University of New York system, and her legacy of activism continues as her students, now on the faculties of universities across the nation, engage in important work globally."-Provided by publisher.